ANALISIS FILSAFAT PENDIDIKAN PERENIALISME PEMIKIRAN ROBERT MAYNARD HUTCHINS DALAM PENDIDIKAN KARAKTER DI SEKOLAH DASAR - Rosmi, St.; Idawati, Idawati; Sayadi, Hamdia (Elementar : Jurnal Pendidikan Dasar, 2024)
This work aims to discover Robert Maynard Hutchins' thoughts on character education in elementary schools from a perpetual perspective. Teachers can use this research to teach character education by utilizing the idea of perennials, which is very important for developing children's character. This research uses a literature study methodology combined with qualitative descriptive techniques. The perennial school of thought considers how humans must evolve with the times. The perennial philosophy approach to character education emphasizes how humans behave according to the good values inherent in themselves. Because elementary school education is a foundation for higher education, character education is most appropriate if started at that level. The concept of perennialism in character education emerged as a response to the contemporary cultural crisis. The philosophy of perennial prioritises efforts to return to the past, especially rebuilding ideals and ideas that were once a strong way of looking at the world. Through character education, these values and ideals of life can be restored to ensure that future generations maintain their identity as an Indonesian nation. One of the options that must be used in elementary school character education is the core of the perennial philosophy.